Design and Development of Nanoparticle-loaded In-situ Gel for Enhanced and Sustained Ophthalmic Delivery - D’Souza, Anupriya; Pissurlenkar, Raghuvir R.S. (Drug Delivery Letters, 2025)
BackgroundFlurbiprofen, a non-selective COX inhibitor utilized for managing mild to moderate pain and inflammation, operates through reversible inhibition of both COX-1 and COX-2 pathways. However, as a BCS class II drug, it exhibits limited aqueous solubility, leading to suboptimal ocular bioavailability and a brief corneal contact.ObjectivesThe goal of this study was to amplify the aqueous solubility of Flurbiprofen by formulating it into a nanosuspension, which was subsequently incorporated into an in-situ gelling system so as to extend the ocular residence time and to achieve sustained drug release.MethodsNanosuspensions were crafted through the anti-solvent precipitation ultra-sonication method. The assessment included parameters, such as particle size, surface morphology, XRD, and FT-IR. The optimized nanosuspension was then incorporated into a pH-sensitive in-situ gel.ResultsThe developed formulation was stable and showed enhanced contact time, minimizing the frequency of administration. Morphological analysis unveiled spherical drug nanoparticles in the nanosuspension without any signs of aggregation, supported by high-resolution transmission electron microscopy. The ex vivo permeation studies showed a drug release of 83.48%, indicating good permeation and histopathology, and isotonicity indicated no ocular irritation and tissue damage.ConclusionThe design and development of Flurbiprofen nanosuspension were found to be liquid at the formulated pH and formed gel due to changes in bonds between polymers. In-situ ocular gels minimize the risk of systemic absorption of the drug, as they are designed to stay localized on the ocular surface and within the eye. An optimum point can be reached in the shortest time with minimum efforts to achieve desirable rheological and in-vitro release properties for in-situ gelling systems.
Keywords: anti-inflammatory